Pengaruh Debt To Equity Ratio, Total Asset Turnover, Net Profit Margin dan Struktur Aktiva terhadap Harga Saham: Studi Empiris pada Perusahaan Sub Sektor Pertambangan Batu Bara yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Eka Lonia; Slamet Mudjijah (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
This study aims to determine the effect of Debt to Equity Ratio, Total Asset Turnover, Net Profit Margin And Asset Structure on Stock Price Coal Mining Sub-Sector Companies Listed in the Indonesia Stock Exchange for the 2019-2023 Period. The samples for this research are 23 coal mining sub-sector companies listed on the Indonesia Stock Exchange before 2019. The analysis method used is multiple linear regression analysis using a statistical test tools, namely Statistical Package for the Social Science (SPSS) version 26.0 and Microsoft Excel 2021. The data used is secondary data in the form of complete financial reports during the study period. The results showed that the variabel Debt to Equity Ratio, Total Asset Turnover effect on Stock Prices. Net Profit Margin And Asset Structure have no significant effect on Stock Price.